Evolution and future of the Lusi mud eruption inferred from ground deformation. Issue 6 (21st March 2013) - Rudolph, M. L.; Shirzaei, M.; Manga, M.; Fukushima, Y.
Abstract [1] The ongoing eruption of the Lusi mud volcano in East Java, Indonesia offers the unprecedented opportunity to study a large eruption from its beginning to its eventual end. We use new observations of ground deformation obtained from multitemporal interferometric analysis of L‐band synthetic aperture radar data to show that Lusi will stop erupting much sooner than previously anticipated. Using principal component analysis, we find that the rate of ground deformation, and by implication, pressure in the mud source region, has been decaying exponentially with an e‐folding time scale of 2.1 ± 0.4 years. We anticipate that discharge will decrease to 10% of the present rate in 5 years.